UR_GERICHTE 2013_OG BI 13 10 vom 30. September 2013 , 2013_OG BI 13 10. Strafprozessordnung. Art. 8 und Art. 11 Ziff. 1 lit. a EUeR. Art. 61 lit. a, Art. 62 Abs. 1, Art. 107 Abs. 1 lit. d, Art. 205 A... - UR Obergericht (2013)
Strafprozessordnung. Art. 8 und Art. 11 Ziff. 1 lit. a EUeR. Art. 61 lit. a, Art. 62 Abs. 1, Art. 107 Abs. 1 lit. d, Art. 205 Abs. 1 und Art. 355 Abs. 1 StPO.